2001
DOI: 10.1254/jjp.86.183
|View full text |Cite
|
Sign up to set email alerts
|

Long Term Effects of Toki-shakuyaku-san on Brain Dopamine and Nerve Growth Factor in Olfactory-Bulb-Lesioned Mice

Abstract: ABSTRACT-We used olfactory-bulb-lesioned mice induced by intranasal irrigation with zinc sulfate as a model of dementia, to investigate the effects of Toki-shakuyaku-san (TSS) on monoamines and nerve growth factor (NGF) in brain regions. TSS was given daily through the drinking water for either 1, 2, 3, 4 or 8 weeks from the day after olfactory lesion. The administration of TSS significantly suppressed the decrease of 3,4-dihydroxyphenyl acetic acid (DOPAC) and homovanillic acid (HVA) in olfactory bulb of olfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 26 publications
1
15
1
Order By: Relevance
“…DSS can make NGF contents increase at 1 and 2 weeks and within 3 weeks, the expression returns to baseline [46]. Administration of DSS could decrease ChAT activity significantly in the cerebral cortex and the DH of ovariectomized mice along with a decrease of NE contents [47].…”
Section: The Effect On the Neurotransmitter And The Central Nervous Smentioning
confidence: 97%
See 1 more Smart Citation
“…DSS can make NGF contents increase at 1 and 2 weeks and within 3 weeks, the expression returns to baseline [46]. Administration of DSS could decrease ChAT activity significantly in the cerebral cortex and the DH of ovariectomized mice along with a decrease of NE contents [47].…”
Section: The Effect On the Neurotransmitter And The Central Nervous Smentioning
confidence: 97%
“…prevents the reduction of dopamine (DA) metabolites, dihydroxyphenylacetic acid (DOPAC), and homovanillic acid (HVA) in olfactory-bulb-lesioned mice [46]. DSS has been shown to improve memory impairment and acetylcholine and norepinephrine in the cerebral cortex and hippocampus [47].…”
mentioning
confidence: 99%
“…It has been reported that TSS increases NGF (1), has an antioxidant action, and has a prophylactic effect against free radical-mediated neurological disease associated with aging (2,3). Recent pharmacological studies revealed that TSS differentially enhances release of T helper 1 cytokines from peripheral blood mononuclear cells but not from decidual mononuclear cells (4).…”
Section: Introductionmentioning
confidence: 99%
“…A useful strategy of addressing this problem is to administer drugs that either enhance the action of endogenous neuritogenic substances such as NGF or increase the expression of these substances in the central nervous system (1). Oral administration of Tokishakuyaku-san, a Chinese traditional medicine, has been reported to increase NGF content in olfactory-bulblesioned mice (2). Several synthetic compounds (3 -5) and natural products (6 -8) have been shown to enhance the action of NGF in neurite outgrowth from PC12 cells.…”
mentioning
confidence: 99%